ECO-DESIGN OF INTEGRATE SYSTEM OF DRYING AND SEPARATING OF OLIVE RESIDUES IN OLIVE OIL INDUSTRY - Abdellatif LAJDEL Pr. Mohamed MAZOUZI, Mohammed LAJDEL & Pr. Mina Bakasse (International Journal of Research Science and Management, 2017)
The objective of this research is optimizing a process of recycling residues called olive cake (stones) for renewable energy use and Pomace for animal feed industry use. This study includes a drying and separation of solid residues from pulp and store final product for an expedition to recommended user. Drying will proceed continuously in parallel with the existing production process of olive oil.